2016
DOI: 10.1182/blood-2016-02-698951
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of germ line JAK2 mutations E846D and R1063H in hereditary erythrocytosis with megakaryocytic atypia

Abstract: • Cells expressing JAK2 E846D or R1063H exhibit pathologic STAT5 activation in the specific context of EPOR.• Cooperation of germ line JAK2 mutations E846D and R1063H defines a JAK2-signaling threshold for induction of erythrocytosis.The role of somatic JAK2 mutations in clonal myeloproliferative neoplasms (MPNs) is well established. Recently, germ line JAK2 mutations were associated with polyclonal hereditary thrombocytosis and triple-negative MPNs. We studied a patient who inherited 2 heterozygous JAK2 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 24 publications
0
37
0
1
Order By: Relevance
“…Activation of the EPO–EPO-receptors complex turns on the JAK2 signaling pathway, resulting in canonical activation of STAT5 by phosphorylation. 32 , 33 The JAK2 pathway also activates multiple secondary signaling pathways, including MAPKs and PI3K, in frequently studied cell types such as erythrocytes, neurons, astrocytes. 34 , 35 Thus, we examined the downstream signaling pathways that might contribute to the neuroprotective effect of MK-X.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the EPO–EPO-receptors complex turns on the JAK2 signaling pathway, resulting in canonical activation of STAT5 by phosphorylation. 32 , 33 The JAK2 pathway also activates multiple secondary signaling pathways, including MAPKs and PI3K, in frequently studied cell types such as erythrocytes, neurons, astrocytes. 34 , 35 Thus, we examined the downstream signaling pathways that might contribute to the neuroprotective effect of MK-X.…”
Section: Resultsmentioning
confidence: 99%
“…We identified a novel JAK2 mutation at kinase domain that is predicted to result in STAT5 activation, as suggested by a previous study that showed a mutation in the same residue, JAK2 p.Arg1063His, associated with STAT5 phosphorylation and increase of CFU-E formation, in addition to in silico modeling, which predicted a facilitation of the active conformation of JH1 ( 38 ).…”
Section: Discussionmentioning
confidence: 57%
“…WT cell line ( Figure 2C ) and erythrocytosis (E846D and R1063H), 19 but our data also suggest that germ line mutations outside the core regulatory domain can alter the EPO-sensing properties of cells and therefore may provide proliferation advantage. Because the JAK2 FERM domain is required for EPOR association and consequent relief of inhibitory conformation of the kinase domain that leads to JAK2 activation, 20,21 the molecular basis of this activation remains to be elucidated.…”
Section: V617fmentioning
confidence: 55%